2016
DOI: 10.1007/s00280-016-3198-0
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I study of intravenous PI3K inhibitor copanlisib in Japanese patients with advanced or refractory solid tumors

Abstract: Purpose To evaluate the safety, tolerability, pharmacokinetics, and efficacy of the intravenously administered pan-PI3K inhibitor copanlisib in Japanese patients with advanced or refractory solid tumors.MethodsA Phase I open-label study in Japanese patients with advanced or refractory solid tumors was carried out. Patients received a single intravenous dose of either copanlisib 0.4 mg/kg or copanlisib 0.8 mg/kg, dosed intermittently on days 1, 8, and 15 of a 28-day cycle. Safety was monitored throughout the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 23 publications
1
29
0
Order By: Relevance
“…Stage 2 results also showed good safety and preliminary efficacy of taselisib in combination with fulvestrant, particularly in the case of the patient who had a PR, whose duration of response was >600 days, suggesting promising efficacy for this combination. The common treatment‐related AE observed in this stage of the study were diarrhea, stomatitis, rash, dry skin, and colitis, which are similar to the AE observed in stage 1 and in global Phase I studies of taselisib monotherapy and in studies of other PI3K inhibitors . All the treatment‐related SAE were considered manageable and patients recovered or improved with appropriate treatment and interruption or reduction of taselisib dosing.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Stage 2 results also showed good safety and preliminary efficacy of taselisib in combination with fulvestrant, particularly in the case of the patient who had a PR, whose duration of response was >600 days, suggesting promising efficacy for this combination. The common treatment‐related AE observed in this stage of the study were diarrhea, stomatitis, rash, dry skin, and colitis, which are similar to the AE observed in stage 1 and in global Phase I studies of taselisib monotherapy and in studies of other PI3K inhibitors . All the treatment‐related SAE were considered manageable and patients recovered or improved with appropriate treatment and interruption or reduction of taselisib dosing.…”
Section: Discussionsupporting
confidence: 64%
“…The results from stage 1 suggested that taselisib had good tolerability, with the common treatment-related AE being diarrhea, rash, stomatitis, headache, and decreased appetite; these were consistent with AE seen in the previous taselisib global Phase I study 14 and studies of other PI3K inhibitors. [15][16][17][18] All treatment-related SAE resolved or improved with dosage reduction, interruption, or discontinuation of treatment. Taselisib monotherapy was associated with 2 PR, all of which were in patients with PIK3CA-mutated tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common treatment-related AEs included nausea and transient hyperglycemia [126]. In a phase I study among Japanese patients with advanced or refractory solid tumor, MTD of 0.8 mg/kg was also observed; the most frequent AEs were hyperglycemia, hypertension, and constipation [127]. A phase I, dose-escalation study of copanlisib in combination with gemcitabine or cisplatin plus gemcitabine (CisGem) recommended copanlisib 0.8 mg/kg for patients with advanced cancer.…”
Section: Bay 80-6946 (Copanlisib)mentioning
confidence: 99%
“…The compound possesses a small size that can be well compatible with the active sites of both the 2 kinase isoforms. In contrast, the larger inhibitor Copanlisib () was suggested to have a strong selectivity for PI3K β over PI3K α ( S = −0.34 < 0).…”
Section: Resultsmentioning
confidence: 94%